The causal effect of option pay on corporate risk management - Bakke, Tor-Erik; Mahmudi, Hamed; Fernando, Chitru S.; Salas, Jesus M. (Journal of Financial Economics, 2016)
This study provides strong evidence of a causal effect of risk-taking incentives provided by option compensation on corporate risk management. We utilize the passage of Financial Accounting Standard (FAS) 123R, which required firms to expense options, to investigate how chief executive officer option compensation affects the hedging behavior of oil and gas firms. Firms that did not expense options before FAS 123R significantly reduced option pay, which resulted in a large increase in their hedging intensity compared with firms that did not use options or expensed their options voluntarily prior to FAS 123R.